PRINCIPLES OF BUILDING LEGAL STATE IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2026)
This scientific article analyzes the theoretical foundations, constitutional principles and their socio-philosophical essence of the process of building legal state in Uzbekistan. The inextricable connection of the concept of a social state with a legal state, its role in ensuring human rights and freedoms, issues of social justice and sustainable development are revealed. Also, the specific aspects and prospects of building legal state in the national development model are highlighted.